Hubungan Tingkat Pengetahuan Kesehatan Gigi Mulut dan Perilaku Perawatan Gigi Pada Anak Usia 10-14 Tahun - Simaremare, Jennifer Priskila Sabatany; Wulandari, Imanuel Sri Mei (Jurnal Keperawatan Muhammadiyah, 2021)
Background: Oral disease is a serious global health problem and can affect all age groups including children. The results of the 2018 Riskesdas stated that the largest proportion of dental problems in Indonesia were damaged, cavities and sick teeth (45.3%).Objective: to  describe the knowledge, behavior and relationship between the level of knowledge of oral health and dental care behavior in children aged 10-14 years.Methods:  The research design was cross sectional. The research instrument consisted of a knowledge and behavior questionnaire created in google form. The research sample consisted of 50 children aged 10-14 years in East Bekasi who were taken by random sampling. This study uses a frequency distribution to describe the knowledge and behavior of the respondents, and analysis tests to determine the relationship between the level of knowledge of oral health and dental care behavior in children. The data were analyzed using the Spearman Rho.Results:  The results showed a significance value of 0.01 <0.05, thus it can be concluded that there is a relationship between knowledge and oral health behavior in children aged 10-14 years.Conclusion:  It is recommended that parents and schools collaborate in providing regular oral health education to children.